THE EFFECT OF INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE IN THE ASEAN TELECOMMUNICATIONS SECTOR - Christandy Adriel (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2020)
Telecommunication sector plays an important role in people’s life, but its service in ASEAN nations are not as good as other nations. Currently, ASEANs telecommunication sector of financial performance (FP) is on a poor level and needs to be improved. Intellectual capital (IC) can increase FP. Every IC's component affects the FP, and this was tested on this research to see which component of IC is good to be invested to increase company’s FP. Independent variables used on this research are Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Relational Capital Efficiency (RCE), and Capital Employed Efficiency (CEE). The dependent variable is Return on Assets (ROA). This research used pooling data method from financial statements of ASEAN telecommunication company in the period of 2011 to 2018. The number of samples which fulfills the criteria were 273 samples. SPSS 20th version was used to analyses the data. The results indicate that FP is affected positively and significantly by HCE and CEE. However, SCE has a negative effect on FP significantly, while RCE does not affect FP. Keywords: Intellectual Capital, Financial Performance, E-VAIC, ASEAN Telecommunication.